Teachers' Moral Dilemma in the Digital Age from the Perspective of Deontological and Consequentialist Ethics - Hendra, Jeli; Fariska Nurjannah; Muhamad Yahya (Sekolah Tinggi Agama Islam Darul Qur'an Payakumbuh, 2025)
Digital transformation in education presents new moral challenges for teachers, especially in maintaining academic integrity, protecting students' personal data, and fairness in technology-based learning processes. This article aims to analyze the moral dilemmas faced by teachers in the digital era through deontological and consequentialist ethical approaches. This research uses a literature study method with a qualitative-descriptive approach, reviewing literature on moral philosophy, professional ethics, and digital education practices. The results of the analysis show that teachers often face complex ethical choices, such as adjusting values due to combined access to technology or students' use of artificial intelligence. Deontological ethics emphasizes the importance of adhering to universal moral principles, while consequentialist ethics prioritizes the positive impact of actions. Integration of both is recommended to enable teachers to make fair and responsible decisions in the digital context. This study recommends strengthening digital ethics education in teachers' professional training as well as the establishment of education policies that are adaptive to technological dynamics. With a reflective and comprehensive ethical approach, teachers can maintain their moral role as educators and character building agents amidst the complexity of the digital world.